Situating a public funding experiment within the landscape of political ideas about the non-profit sector. (23rd March 2017) - Levasseur, Karine; Frankel, Sid
Abstract : This article examines a recent funding experiment in one sub-national jurisdiction in Canada. Implemented as a two-year pilot project, this experiment included multi-year funding to non-profit organisations, a single window application portal and rationalisation of reporting requirements when multiple departmental funders are present. To understand the experiment, we situate it in the context of seminal political ideas about the non-profit sector. We assess whether it is a movement away from new public management (NPM) or an adoption of the marketisation of public services and use of the non-profit sector as an instrument to reverse civic decline of third-way politics or if it represents increased collaborative governance practices. We argue that while this represents a meaningful departure from NPM, it is only a partial reflection of third-way and collaborative governance as well as a pragmatic response to situational factors.